Armed Conflict and Poverty in Antioquia Colombia - Maya Taborda, María; Muñetón Santa, Guberney; Horbath Corredor, Jorge Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The aim of this paper is to explore the relationship between armed conflict and poverty in the department of Antioquia, Colombia. Drawing on various official and press databases, we present a spatial analysis made up of quantitative and qualitative data. We highlight the spatial relationships between armed conflict and poverty, showing how these relationships are expressed unevenly in the territory. The paper focuses on two spatial units of analysis, Urabá and Oriente Antioqueño, which have distinct dynamicsand results in terms of armed conflict and poverty. To conclude, we offer some avenues of research to better understand the phenomenon of poverty in places affected by armed conflict.